Analisis Peran Underwriter dalam Menyeleksi Risiko pada Produk Asuransi Jiwa Syariah di Allianz Cabang Kota Padang - Aida Lasmi; Muhammad Arif; Juliana Nasution (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims at the role of the underwriter in selecting in sharia life insurance products, knowing the obstacles encountered by the underwriter in selecting the risk and the solutions applied to overcome these obstacles, and knowing the underwriting process of sharia life insurance at allianz padang city branch . The type of research used is descriptive research, with a qualitative approach. The conclusions of this study briefly are: (1) Underwriters have an important role in insurance companies because underwriters determine whether the insurance coverage can be accommodated by the company or not. (2) Obstacles encountered by underwriters in selecting risks are the availability of incomplete participant data, previous experience data of the insured and prospective insured not providing the desired budget and benefits, while the solution is to contact the agent concerned to obtain additional information needed by the underwriter, apply analysis to groups of prospective insurance participants as new participants, and provide standard premium rates and benefits. (3) The underwriting process begins when marketing applies for SPPA until the issuance Keywords: Underwriting, Underwriter, Sharia Life Insurance